If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5X + 6) + -1(-3x + 10) = 2x + -4 Reorder the terms: (6 + 5X) + -1(-3x + 10) = 2x + -4 Remove parenthesis around (6 + 5X) 6 + 5X + -1(-3x + 10) = 2x + -4 Reorder the terms: 6 + 5X + -1(10 + -3x) = 2x + -4 6 + 5X + (10 * -1 + -3x * -1) = 2x + -4 6 + 5X + (-10 + 3x) = 2x + -4 Reorder the terms: 6 + -10 + 5X + 3x = 2x + -4 Combine like terms: 6 + -10 = -4 -4 + 5X + 3x = 2x + -4 Reorder the terms: -4 + 5X + 3x = -4 + 2x Add '4' to each side of the equation. -4 + 5X + 4 + 3x = -4 + 4 + 2x Reorder the terms: -4 + 4 + 5X + 3x = -4 + 4 + 2x Combine like terms: -4 + 4 = 0 0 + 5X + 3x = -4 + 4 + 2x 5X + 3x = -4 + 4 + 2x Combine like terms: -4 + 4 = 0 5X + 3x = 0 + 2x 5X + 3x = 2x Solving 5X + 3x = 2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3x' to each side of the equation. 5X + 3x + -3x = 2x + -3x Combine like terms: 3x + -3x = 0 5X + 0 = 2x + -3x 5X = 2x + -3x Combine like terms: 2x + -3x = -1x 5X = -1x Divide each side by '5'. X = -0.2x Simplifying X = -0.2x
| 3(x+3)-7=4(x-2)+5 | | 6(x+13)=7x-8-3x | | 0.009x+0.2(500-x)=0.03*500 | | 3Y-2Z=-5 | | 4[x-1]=0 | | sin(3pix)=1 | | 3x(1+x)=0 | | 5x*2-7x-24=0 | | (x-3)(x-5)=64 | | (x-3)(x-5)=74 | | (x-3)(x-5)=84 | | (x+3)(x-5)=84 | | 3*x-x*log(x)=log(e^5) | | 3x-xln(x)=lne^5 | | 5x-7x-24=0 | | 4d^2-16-8d-d^2=0 | | x^3-24x^2+180x-424=0 | | 3x-xln(x)-9=(-4) | | 48=5x-28 | | 5+7x=9x-12 | | Log(x)12=5 | | y*(-3-y)=-10 | | -3y-y=-10 | | 15y-y=56 | | 3x^2-6x+1.625=0 | | f(1/2x)*(1/2x) | | 681=X+0.3X | | (0.45*1.6x)+(0.55*x)=6 | | (14/120)x(14/120)x(14/120) | | (0.45*1.6x)+(0.55*x)=3 | | 4x-9=ax-3a | | 4x-9=ax-3ax |